Comparative metabolomics provides novel insights into correlation between dominant habitat factors and constituents of Stellaria Radix (Stellaria dichotoma L. var. lanceolata Bge.) - Li, Zhenkai; Wang, Hong; Feng, Lu; Song, Le; Lu, Yongping; Li, Hongying; Li, Yanqing; Tian, Gege; Yang, Yan; Li, Haishan; Mei, Xiangui; Peng, Li (Frontiers in Plant Science, 2022)
Stellaria dichotoma L. var. lanceolata Bge. (SDL) is the original plant of the traditional Chinese medicine Yinchaihu (Stellaria Radix). It is mainly distributed in the arid desert areas of northwest China and has been developed as an important industrial crops and products in Ningxia. This study aims to analyze the effects of different origins on SDL metabolites and herb quality, as well as to screen the dominant habitat factors affecting SDL in different origins. In this study, the metabolites of SDL from nine different production areas were analyzed by ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF MS), and field investigations were conducted to record thirteen habitat-related indicators. Results showed that 1586 metabolites were identified in different origins, which were classified as thirteen categories including lipids, organic acids and organic heterocyclic compounds derivatives. Multivariate statistical analysis showed that the metabonomic spectra had different characteristics in different origins. What’s more, co-expression network correlation analysis revealed that three metabolites modules(MEturquoise, MEbrown and MEblue) were more closely with the habitat factors and 104 hub metabolites were further screened out as the habitat-induced metabolite indicators. Besides, soil texture, soil pH value and soil total salt content were found as the dominant habitat factors which affect SDL metabolites. In conclusion, this study showed different habitat factors had various effects on SDL’s quality and established relationship between them, which provide reference for revealing SDL's genuineness formation mechanism and guiding industrial crops practical production by habitat factors selection.